New capital cities in the Global South: Post-modernist context, modernist layout in Nigeria and Brazil - Rego,Renato Leão (2021)
Abstract This paper contextualizes Abuja’s planning history (Nigeria, 1979-1981) and Palmas (Brazil, 1989), considering networks of knowledge, travelling ideas, and the planners’ tool-kit. It analyses these new capital cities’ layouts through a more global reading of planning history. It argues that their plans, created out of political and economic imperatives and entrusted with transformative expectations, did not abandon the hegemonic modernist models in post-modernist, post-colonial times, regardless of the planners’ backgrounds. Global ideas concealed cultural sensibilities in both cases as local and foreign professionals developed comparable planning proposals in equivalent responses to the international frameworks.